2007
DOI: 10.1002/cbic.200700009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Conformation of the Human VDAC1 N‐Terminal Peptide, a Protein Moiety Essential for the Functional Properties of the Pore

Abstract: Mitochondrial porin or VDAC (voltage-dependent anion-selective channel) is the most abundant protein in the mitochondrial outer membrane. The structure of VDAC has been predicted to be a transmembrane beta-barrel with an alpha-helix at the N terminus. It is a matter of debate as to whether this putative alpha-helix plays a structural role as a component of the pore walls or a function in the pore activity. We have synthesised the human VDAC1 (HVDAC1) N-terminal peptide Ac-AVPPTYADLGKSARDVFTK-NH2 (Prn2-20) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 75 publications
(97 reference statements)
12
53
0
1
Order By: Relevance
“…The Nterminal sequence is located inside the channel, forming a partial obstruction of the wide pore, possibly exerting a structural reinforcement to the channel walls. In agreement with this finding, CD and NMR spectroscopy of the isolated N-terminal peptide showed that there is the need of a special environment to force the peptide in an ordered a-helix secondary structure [20]. In water, for example, it is usually disordered.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The Nterminal sequence is located inside the channel, forming a partial obstruction of the wide pore, possibly exerting a structural reinforcement to the channel walls. In agreement with this finding, CD and NMR spectroscopy of the isolated N-terminal peptide showed that there is the need of a special environment to force the peptide in an ordered a-helix secondary structure [20]. In water, for example, it is usually disordered.…”
Section: Introductionsupporting
confidence: 63%
“…This structure represents an addition to the b-barrel pore structure and was proposed to have functionally relevant properties [20][21][22][23][24][25][26]35]. It has been recently proposed that the final N-terminal sequence (i.e.…”
Section: Role Of the Vdac N-terminusmentioning
confidence: 99%
“…As such, this helix is ideally positioned to regulate the conductance of ions and metabolites passing through the VDAC pore. These structural and other studies (De Pinto et al, 2007) further indicate that the helical region of the VDAC N-terminal domain forms a distorted α-helix that does not span the whole sequence but only part of it. Although these recently determined VDAC1 structures suggest that the hydrophilic N-terminus of the protein is nestled within the pore (Bayrhuber et al, 2008;Hiller et al, 2008;Ujwal et al, 2008), other approaches point to the N-terminal α-helix as being exposed to the cytoplasm (De Pinto et al, 2003), to cross the membrane (Colombini, 2004) or to lie on the membrane surface (Reymann et al, 1995).…”
Section: Introductionmentioning
confidence: 59%
“…The N-terminal domain of VDAC1 has been the object of considerable interest and was proposed to possess functionally relevant properties (Colombini et al, 1987;De Pinto et al, 2007;Peng et al, 1992;Stanley et al, 1995;Ujwal et al, 2008;Yehezkel et al, 2007). VDAC provides the major pathway for nucleotides and other metabolites moving across the OMM.…”
Section: Resultsmentioning
confidence: 99%
“…The FLAG1, which is 11-20 residues from the N-terminus, will most likely have a trans exposure (see Fig. 1); especially if the Nterminus is as dynamic as proposed [8,13,[22][23][24][25]. Residues 1-10 continue through the lumen towards exposure of the extreme Nterminal residue to the cis side.…”
Section: Immunoprecipitation Of Intact and Disrupted Mitochondriamentioning
confidence: 99%